Intravenous glyburide in medical and endovascular-treated large-core stroke: a subgroup analysis of the CHARM randomized clinical trial - Kimberly, William Taylor; Saver, Jeffrey L.; Campbell, Bruce C.V.; Albers, Gregory W.; Molyneaux, Bradley J.; Hinson, H.e.; Rocha, Marcelo; Mittal, Shilpi; Bacchi, Stephen; Sharma, Gagan; Cordonnier, Charlotte; Steiner, Thorsten; et al. (Annals of neurology, 2025)
Objective The Glibenclamide for Large Hemispheric Infarction Analyzing mRS and Mortality (CHARM) trial enrolled participants with large hemispheric infarction, randomized to a placebo or intravenous glyburide. Our objective in this post-hoc study was to evaluate the relationship between baseline stroke volume and the potential efficacy of i.v. glyburide. Methods Participants enrolled in CHARM and aged ≤70 years were included if a <125 ml ischemic core lesion volume was measured by computed tomography perfusion or diffusion magnetic resonance imaging. The primary endpoint was a shift analysis on the 90-day modified Rankin Scale. Independent variables included age, sex, baseline National Institutes of Health Stroke Scale, world region, tissue plasminogen activator, and endovascular thrombectomy. Results A total of 147 participants with a baseline large-core stroke volume <125 ml were available for this analysis (mean age 58 years, 37% women, baseline National Institutes of Health Stroke Scale 18, and the time to study drug was 9.1 ± 2.1 h). The median baseline core volume of 92 mL (IQR 81-107 ml) did not differ by treatment arm. The i.v. glyburide-treated participants had a favorable shift in outcome relative to the placebo (adjusted common odds ratio 2.11, 95% CI 1.10-4.01, p = 0.02). In patients who underwent endovascular thrombectomy, i.v. glyburide-treated subjects had a favorable outcome (adjusted common odds ratio 8.19, 95% CI 1.60-42.0, p = 0.01), fewer decompressive craniectomies (0% vs 25%, P = 0.02), less midline shift (4.2 ± 2.5 mm vs 7.6 ± 5.5 mm, p = 0.02), and lower 90-day mortality (5.6% vs 31%, p = 0.05) compared with the placebo, respectively. Interpretation This post-hoc analysis of the CHARM trial provides hypothesis-generating evidence that i.v. glyburide may improve outcome in large-core stroke <125 ml, especially among endovascular thrombectomy-treated patients. These results require confirmation in a prospective randomized clinical trial. ANN NEUROL 2025;98:616-624